Analysis of The Form And Symbolic Meaning of The Temu Nganten Tradition In The Javanese Community of Tanjung Rasa Hamlet, Tanjung Harapan Village, Ulok Kupai District, Bengkulu Utara Regency, Bengkulu Province - Ainur Rohmah; Irwan Satria; Heny Friantary (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2025)
This study aims to analyze the form and symbolic meaning of the Temu Nganten tradition in the Javanese community of Tanjung Rasa Hamlet, Tanjung Harapan Village, Ulok Kupai District, Bengkulu Utara Regency, Bengkulu Province. This tradition is part of the series of rituals in Javanese traditional wedding ceremonies, involving various media and imbued with cultural symbols and values. Using a descriptive qualitative approach, this research collects data through interviews, observations, and documentation to understand the visual elements and deeper meanings of the Temu Nganten tradition. The findings reveal that the Temu Nganten tradition encompasses verbal symbols such as the chanting of Shalawat Asyraqal and Kebo Ghiro, as well as non-verbal symbols such as the balangan sirih ritual, stepping on an egg (pidhak hantiga), sindur, sembah sungkem, and dahar klimah. These symbols reflect values of loyalty, harmony, respect, and readiness to start a harmonious married life for the couple. This study emphasizes the importance of preserving the Temu Nganten tradition as part of the cultural identity of the Javanese community and as an effort to safeguard the continuity of local cultural heritage amid ongoing modernization.